2012
DOI: 10.1074/jbc.m111.263806
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PDE10 and PDE11 Phosphodiesterases

Abstract: Background:The cyclic nucleotide phosphodiesterases PDE10 and PDE11 contain putatively regulatory GAF domains with unknown function. Results: Synthetic GAF domain ligands can activate both PDEs. Conclusion: PDE10 is activated by cAMP, whereas the physiological ligand of the PDE11 GAF domains remains unknown. Significance: This is the first demonstration of a functional role of the PDE10 and PDE11 GAF domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 38 publications
1
70
0
Order By: Relevance
“…The second messenger cAMP is the key mediator of dopaminergic input in these neurons. PDE10A, a phosphodiesterase with clear preference for degradation of cAMP (6), has been shown to be primarily expressed in medium spiny neurons by in situ hybridization and immunological techniques (9,10,39). Furthermore, subcellular fractionation indicated that the protein was associated with synaptosomal membranes (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second messenger cAMP is the key mediator of dopaminergic input in these neurons. PDE10A, a phosphodiesterase with clear preference for degradation of cAMP (6), has been shown to be primarily expressed in medium spiny neurons by in situ hybridization and immunological techniques (9,10,39). Furthermore, subcellular fractionation indicated that the protein was associated with synaptosomal membranes (10).…”
Section: Discussionmentioning
confidence: 99%
“…PDE10 is encoded by one gene (PDE10A) that gives rise to several splice variants (7,8) of which PDE10A2 appears to be the major neuronal form in various species. The highest expression of PDE10A has been detected in the striatum (6,9) where it is restricted to the GABAergic medium spiny neurons (10 -12). These neurons represent ϳ95% of striatal neurons and integrate cortical glutamatergic input and midbrain dopaminergic signaling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Future work will include pathway-specific characterization of PDE10A inhibitors. Other mechanisms, such as regulation of PDE10A activity by its GAFb domain, PDE10A localization through palmitoylation, and unknown regulation through binding partners of PDE10A (Charych et al, 2010;Jäger et al, 2012;Russwurm et al, 2015), are worth evaluating.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Adapted from Beste and Seifert (2013) of catalytic activity in PDE10 is characterized by two uncommon features. First, the PDE10 GAF domain tandem binds cAMP with higher affinity than cGMP (Jäger et al 2012), which indicates that GAF domains are not necessarily cGMP-specific. Second, although cAMP binding to PDE10 GAF-B enhances catalytic activity for cGMP hydrolysis at low concentrations, cAMP concentrations higher than 0.1 μM completely inhibit cGMP hydrolysis (Jäger et al 2012).…”
Section: Traditional Classification Of Pdesmentioning
confidence: 99%